2014
DOI: 10.1007/s12032-014-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA expression profiles of EGFR exon 19 deletions in lung adenocarcinoma ascertained by using microarray analysis

Abstract: Studies showed that long chain non-coding RNAs (lncRNAs) involved in the development and progression of lung cancer. However, the mechanisms of EGFR exon 19 deletion in lung adenocarcinoma were unclear. Lung adenocarcinoma was divided into EGFR exon 19 deletion group and EGFR wild-type group. We studied the differential expression profiles of lncRNAs in EGFR exon 19 deletion in lung adenocarcinoma by high-throughput microarray. Using abundant and varied probes, we were able to assess 30,586 lncRNAs and 26,109 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Similar to previous studies, BANCR was also suggested to influence cell migration in colorectal cancer, probably via modulation of EMT (Guo et al 2014). In papillary thyroid carcinoma, BANCR knockdown reduced cell proliferation and moderately induced apoptosis in a cell line (Wang et al 2014d). No effect on cellular metastatic potential was observed.…”
Section: Bancrsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to previous studies, BANCR was also suggested to influence cell migration in colorectal cancer, probably via modulation of EMT (Guo et al 2014). In papillary thyroid carcinoma, BANCR knockdown reduced cell proliferation and moderately induced apoptosis in a cell line (Wang et al 2014d). No effect on cellular metastatic potential was observed.…”
Section: Bancrsupporting
confidence: 84%
“…In contrast to NSCLC, BANCR was significantly upregulated in malignant melanoma, colorectal carcinoma, and papillary thyroid carcinoma tissue (Wang et al 2014d;Guo et al 2014;Flockhart et al 2012). In the original study on BANCR, an influence of the lncRNA on melanoma cell migration via regulation of CXCL11 chemokine expression levels was observed (Flockhart et al 2012).…”
Section: Bancrmentioning
confidence: 97%
See 1 more Smart Citation
“…lncRNAs have emerged as novel master regulators of initiation, progression, and response to therapy in a wide variety of solid tumors and hematological malignancies [ 6 ],[ 7 ]. Hundreds of IncRNAs have been associated with lung cancer through gene expression microarrays and massively parallel RNA sequencing of tumor tissues and paired adjacent non-tumor tissues in the lung [ 8 ]-[ 11 ]. As of September 2014, a PubMed search using lncRNA and lung cancer as key words yielded more than a dozen of lncRNAs that have been individually investigated in lung cancer (Table 1 ) [ 8 ],[ 12 ]-[ 38 ].…”
Section: Lncrnas As Novel Master Regulators Of Lung Cancermentioning
confidence: 99%
“…Illumina-developed arrays contained less information on lncRNAs due to their design emphasis on 3′UTR targeting, however several lncRNAs were included under the ‘LOC_” definition. Using this probe-based approach several studies were able to identify lncRNA expression profiles in lung cancer and perform preliminary analysis [ 136 139 ], the results of which have been conveniently collated by lnc2cancer [ 140 ]. However, the discernable drawbacks of such techniques include the lack of discovery and low-expression levels of lncRNAs, thwarting detection efforts.…”
Section: Genome-wide Analysis Of Lncrnas In Luadmentioning
confidence: 99%